The brazilian sugar and alcohol sector: Evolution, productive chain and innovations - Strachman, Eduardo [UNESP]; Pupin, Gustavo Milan [UNESP] (United Nations Publications, 2011)
The sugar and alcohol sector is one of the fastest growing and developing areas of the Brazilian economy, although some specialists worry unduly that sugarcane cultivation will replace food-crop plantations. This article analyses how Brazil and the State of São Paulo became major players in that sector, and expounds a theory on the relevance of innovations for increasing competitiveness, productivity and the number of byproducts. The study analyses global value chains to gauge their importance and gain a better understanding of the sugar and alcohol sector. It shows that the value chain is under national control, unlike most other chains in which Brazil participates. Lastly, the article highlights the most recent innovations in the sector, which reflect a drive to improve competitiveness.
Keywords: Agricultural production; Alcohol fuels; Alcohols; Brazil; Competitiveness; Industrial development; Industrial production; Innovations; Sugar